2015
DOI: 10.1590/1679-78251535
|View full text |Cite
|
Sign up to set email alerts
|

Vibration suppression of a rotating flexible cantilever pipe conveying fluid using piezoelectric layers

Abstract: In this study, the governing equations of a rotating cantilever pipe conveying fluid are derived and the longitudinal and lateral induced vibrations are controlled. The pipe considered as an Euler Bernoulli beam with tip mass which piezoelectric layers attached both side of it as sensors and actuators. The follower force due to the fluid discharge causes both conservative and non-conservative work. For mathematical modeling, the Lagrange-Rayleigh-Ritz technique is utilized. An adaptive-robust control scheme is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Substituting Equations ( 4)- (6) into Equation (1), one can obtain the governing equation for the cantilevered pipe with dry friction: The following assumptions are introduced: (1) the pipe centerline is inextensible;…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Equations ( 4)- (6) into Equation (1), one can obtain the governing equation for the cantilevered pipe with dry friction: The following assumptions are introduced: (1) the pipe centerline is inextensible;…”
Section: Theoretical Modelmentioning
confidence: 99%
“…During vibration, harsh and harmful noise may be generated and the pipe system tends to be fatigued and damaged, which may cause economic losses and serious safety accidents [3]. Therefore, the dynamic analysis and vibration control of pipes conveying fluid have attracted much attention [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the fluid effects on the dynamics of a heat exchanger system must be examined, and they bring the so-called fluid induced vibration. Investigations such as [Papp and Chen (1994), Tian et al (2000), Khajehpoura and Azadib (2015)] have paid attentions to the fluid effect on the dynamic behaviors in a system. It was found that the fluid effect changes markedly the dynamic characteristics of a system.…”
Section: Dynamic Properties Of Coupled Tube-array Structures With Thementioning
confidence: 99%
“…It is generally known that a cantilevered pipe may become unstable and flutter instability would occur when the velocity of the fluid flow in the pipe exceeds a critical value. Indeed, a lot of researchers have endeavored to enhance the stability of cantilevered pipes conveying fluid [7][8][9][10][11][12][13][14][15][16][17], by using either passive or active methods. For instance, Tani et al [12,13] applied a torsional moment to a certain position of the cantilevered fluid-conveying pipe, and then experimentally and numerically studied the suppression effect of the torque on the oscillation responses of the pipe.…”
Section: Introductionmentioning
confidence: 99%